Fraud Pentagon dalam Mendeteksi Fraudulent Financial Reporting pada Perusahaan BUMN - Nur Hidayah K Fadhilah; Siti Rukoyah; Heliani Heliani (Postgraduate Program Merdeka University, 2022)
The purpose of this study is to examine the fraud factors of the pentagon fraud theory in detecting fraudulent financial reporting in state-owned companies for the 2016-2019 period. The independent variables of this research are financial target, financial stability, external pressure, ineffective monitoring, external auditor quality, change in auditor, change in directors frequent number of CEO's pictures, meanwhile the dependent variable of this research is fraudulent financial reporting. The number of samples in the study was 164, which came from 41 companies. Purposive sampling is a sampling technique. Data analysis using logistic regression. The results of the study prove that change in auditor has an influence on fraudulent financial reporting. On the other hand, financial target, financial stability, external pressure, ineffective monitoring, external auditor quality, change in directors dan frequent number of CEO's pictures have no effect on fraudulent financial reporting.DOI: https://doi.org/10.26905/afr.v5i3.7966